Barriers to leisure-time physical activity participation among youth / Nur Adilah Natasya Zawawi and Rozita Abdul Latif - Zawawi, Nur Adilah Natasya; Abdul Latif, Rozita (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Physical activity participation among youth is a growing concern, leading to severe health and economic consequences [1]. Despite global recommendations, many fail to meet the required activity levels due to various barriers. This study identifies key obstacles to youth participation in leisure-time physical activity, examines gender differences, and explores their impact on activity levels [2]. Understanding these barriers is crucial for developing targeted interventions to promote a healthier and more active lifestyle [3]. A survey was conducted with 3138 respondents (172 males, 141 females). Data were analyzed using Jamovi software, employing Chi-Square tests to assess associations between barriers and leisure-time physical activity [4]. A purposive sampling used for individuals that age range 18 and above who attend the interview at FSR Seremban Campus.